THE LANGUAGE USE OF SEX ARTICLES IN WOMEN LIFESTYLE MAGAZINE IN INDONESIA CASE STUDY: COSMOPOLITAN INDONESIA - Sarwono, Dian (Universitas Negeri Yogyakarta, 2019)
The choice of words is one of important aspects in writing articles in printed media. Creative language use in lifestyle magazine may create interest for readers. The purpose of this research is to analyze the language use in sex articles in Cosmopolitan Indonesia. Launched in 1997, Cosmopolitan Indonesia is the first licensed Indonesian women lifestyle magazine and the first women magazine in Indonesia that openly discusses sex. This marks a change in Indonesian printed media. Before the publication of Cosmopolitan, sex and intimacy were only discussed in non-public spheres. Although the topics are discussed openly, the magazine uses special terms to describe man and women genital organs. After 22 years, Cosmopolitan Indonesia is still using the same terms in its sex articles, despite the fact that other women magazines are now discussing sex more openly and most of them are using the medical terms to describe genital organs. The focus of this research is mainly on what factors that consider Cosmopolitan Indonesia to use special terms in sex articles. The methodology will include purposive sampling interview and content analysis of 6 editions of Cosmopolitan Indonesia. The findings of this research may help the media and journalists to be more creative in choosing words for particular articles to attract readers interest, also to established the media unique identity, especially for lifestyle magazine. Pemilihan kata-kata adalah aspek penting dalam penulisan artikel dalam media cetak. Bahasa yang kreatif digunakan dalam penulisan untuk majalah gaya hidup agar menarik perhatian pembaca. Tujuan dari penelitian ini adalah untuk menganalisis penggunaan Bahasa pada majalah Cosmopolitan Indonesia. Diterbitkan tahun 1997, Cosmopolitan Indonesia adalah majalah gaya hidup berlisensi Internasional untuk perempuan pertama dan majalah perempuan pertama di Indonesia yang mendiskusikan topik seks secara terbuka. Hal ini menandai perubahan pada sejarah media cetak di Indonesia. Sebelum terbitnya majalah Cosmopolitan Indonesia, seks dan hubungan intim umumnya tidak didiskusikan secara terbuka pada media cetak. Walaupun topik-topik didiskusikan secara terbuka, majalah ini tetap menggunakan istilah tersendiri untuk menggambarkan alat kelamin lelaki dan perempuan. Setelah 22 tahun, Cosmopolitan Indonesia tetap menggunakan istilah istimewa untuk artikel seks, walaupun majalah perempuan lainnya kita telah membicarakan seks dengan lebih terbuta dan umumnya menggunakan istilah medis untuk menggambarkan alat kelamin. Fokus dari riset ini adalah untuk mengetahui faktor apa saja yang membuat Cosmopolitan Indonesia mempertimbankan untuk memilih istilah khusus dalam penulisan artikel seks. Metodologi yang digunakan adalah purposive sampling interview dan content analysis dari 6 edisi Cosmopolitan Indonesia. Penemuan hasil riset ini diharapkan dapat membantu media dan jurnalis untuk lebih kreatif dalam memilih kata-kata untuk beberapa artikel spesifik untuk menarik perhatian pembaca, juga membentuk identitas unik sebuah media, khususnya majalah gaya hidup.